Determinants of community compositional change are equally affected by global change. (25th June 2021) - Avolio, Meghan L.; Komatsu, Kimberly J.; Collins, Scott L.; Grman, Emily; Koerner, Sally E.; Tredennick, Andrew T.; Wilcox, Kevin R.; Baer, Sara; Boughton, Elizabeth H.; Britton, Andrea J.; Foster, Bryan; Gough, Laura; et al.
Abstract: Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes. Abstract : Synthesising community responses to global change driver treatments is necessary to make predictions of future communities. Across 219 control–treatment comparisons, we find that communities are consistently being impacted by global change treatments, and multiple resource treatments result in the greatest community changes. However, communities are changing in many ways, and there is no ordered progression to these changes.